ENCUMBRANCE ACCOUNTING FOR INDUSTRY. - Hackett, Robert P. (The Accounting Review, 1944)
Abstract The article presents information on encumbrance accounting for industry. As soon as purchase orders or contracts are signed, the resulting obligations should be entered at once as encumbrances of the funds and appropriation affected. This is one of the principles laid down for municipal accounting by the National Committee. But it is just as appropriate for all organizations characteristics which make this kind of accounting desirable. The principle has been generally accepted both in theory and in practice, and has been recognized in laws governing this type of accounting. Inspection of published reports of municipalities shows that the principle is used in their accounts in many cases. The laws of several states show a recognition of the principle. For purposes of control and information, and to avoid possible personal liability, it is important that the records be left with full disclosure at all times of the free unexpended, unencumbered balance of appropriations. To assure that this information will be available, it should be made part of the permanent record. If industrial and commercial businesses had such information available as part of the permanent record it would be helpful and valuable in many instances to managers, directors, stockholders, bankers and others.